Bandwidth clustering for reliable and prioritized network routing using split agent-based method - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2005)
Recent researches have highlighted the importance of developing a network with distributed problem solving abilities thus enhancing reliability with equal share of network resources. While several centralized schemes have been proposed for efficient path marking and capacity reservation, the decentralized approach is one of the motivating reasons for employing adaptive behavior of swarm-based agents. Algorithmically complex problems such as reliable network routing need to be faced with a dynamically adaptive approach. In this work the bandwidth clustering method is presented, a method developed using the split agent-based routing technique (SART). The SART method is applied in the network, performing path marking activating at the same time the bandwidth clustering method by which nodes within paths are clustered with respect to several levels of available bandwidth. A path freshness degree is estimated and modeled in order to ensure reliability of data traffic flow. Thorough examination is carried out for the performance, path survivability and recoverability using a SART-bandwidth clustering scheme.